Update on Hepatitis C - Smolic, Martina; Vcev, Aleksandar; Wu, George Y. (IntechOpen, 2017)
In the past few years, remarkable progress has been made in our understanding of HCV biology, pathogenesis of infection, and structure-function relationships. This has led to quantum advances in clinical efficacy and tolerability. Yet, in spite of this amazing progress, there remain obstacles to widespread successful treatment. These issues include biological failures even with direct-acting agents, lack of options for individual with organ failures, drug-drug interactions, access to medications either due to lack of availability or affordability, and psychiatric and social issues. These problems are likely to remain in the future. Therefore, this book has been created by distinguished faculties from around the world to address the progress in our understanding of HCV infection and to review new treatment options, limitations, and accessibility of new therapeutic options.